Business Model of Maqāṣid Al-Sharī'ah-Based Pesantren: Value Chain Approach and Shared Value Creation - Joni Joni; Ija Suntana; Usep Saepullah; Dedah Jubaedah (International Journal of Nusantara Islam, 2026)
Strengthening the Economic Independence of Islamic boarding schools is a strategic agenda in developing a community-based sharia economy. Although many institutions possess superior business units, their management remains partial, unstructured, and unintegrated within a systematic framework. This condition prevents the Silsilat al-Qīmah (value chain) of pesantren businesses—from production and quality control to distribution—from achieving optimal economic and social value. Therefore, this article aims to formulate an Islamic Boarding School Business Model based on Maqāṣid al-Sharī'ah through a combined approach of Silsilat al-Qīmah and Khalq al-Qīmah al-Musytarakah (Creating Shared Value). Using a qualitative field study method across several schools, data was gathered via in-depth interviews, observations, and documentation, then analyzed thematically by integrating sharia principles as a normative foundation alongside business management instruments. The results show that strengthening the pesantren business model requires institutional consolidation, managerial capacity building, and value chain integration oriented toward distribution fairness, product quality, and sustainability. The Khalq al-Qīmah al-Musytarakah approach emphasizes that economic activities must not only increase institutional income but also empower students and the surrounding community to achieve collective benefits. Ultimately, this article contributes theoretically by offering a conceptual framework for an Islamic Boarding School Business Model based on Maqāṣid al-Sharī'ah that contextually connects Islamic normative values with practical business management. Practically, it serves as a strategic reference for building a just, resilient, and sustainable pesantren economy.